Description of Subjective Welfare of Santri at Islamic Boarding Schools - Mahestining Kaluni Indah Kusuma; Lely Ika Mariyati (Universitas Muhammadiyah Sidoarjo, 2023)
Adolescents need high subjective well-being because adolescence is a transition period from childhood to adulthood so that they are vulnerable to various problems. The same applies to teenage students who live in Islamic boarding schools. This study aims to determine the description of subjective well being in adolescent students at Pondok Pesantren An - Nur Sidoarjo. The number of subjects in this study were 123 students using the proportional stratified random sampling technique from 190 total populations. Collecting data using a Likert scale model on the subjective well being variable. The research analysis uses descriptive analysis method with a quantitative approach and utilizes the help of SPSS 25.0 for Windows. The results of this study indicate that most of the subjective well being students are in the moderate category with a percentage of 38% of 47 students. The next result is a description of subjective well being based on gender and age. Subjective well being based on gender shows that the value of Sig. (2-tailed) 0.023 <0.05, then there is a significant difference between the subjective well being of male students. Subjective well being based on the age factor of the students at the An-Nur Islamic Boarding School can show that the value of Sig. 0.000 <0.05, it can be concluded that the average subjective well being based on age is significantly different.